Latent Tuberculosis: Interaction of Mycobacterium tuberculosis with Macrophages - Adiyaksa, Jongga; Rukmana, Andriansjah (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
Latent TB infection (LTBI) is a state of persistent immune response to Mycobacterium tuberculosis antigen stimulation but does not yet show clinically active TB. Macrophages can eliminate Mycobacterium tuberculosis through various mechanisms. The aim of this research is to determine the interaction of macrophages against Mycobacterium tuberculosis. Of the 116 articles screened, there were 42 articles that were in accordance with this literature study. Results from the studies reviewed It is possible that some individuals diagnosed with LTBI have recovered from the bacteria, while others have a very small chance of being reinfected.Â Granulomas are a pathological sign of Mtb infection. The location of bacteria in the granuloma may influence the immune response necessary to control the infection. Mtb produces lipid and protein effectors that control inflammation and macrophage activity. By preventing Mtb-macrophage interactions and entry into human cells, tuberculosis can be avoided. In addition, many mycobacterial factors play important roles in immune evasion or aid reactivation. The class of proteins encoded by the rpf gene are known as resuscitation promoting factors, which appear to play an important role in reactivation. The Rpf gene is thought to be important in driving mycobacteria out of a dormant (and possibly latent) state.Â Â